Functional Interactions Between rsks-1/S6K, glp-1/Notch, and Regulators of Caenorhabditis elegans Fertility and Germline Stem Cell Maintenance. Issue 10 (1st October 2018) - Roy, Debasmita; Kahler, David J; Yun, Chi; Hubbard, E Jane Albert
Abstract: The proper accumulation and maintenance of stem cells is critical for organ development and homeostasis. The Notch signaling pathway maintains stem cells in diverse organisms and organ systems. In Caenorhabditis elegans, GLP-1 /Notch activity prevents germline stem cell (GSC) differentiation. Other signaling mechanisms also influence the maintenance of GSCs, including the highly-conserved TOR substrate ribosomal protein S6 kinase (S6K). Although C. elegans bearing either a null mutation in rsks-1 /S6K or a reduction-of-function ( rf ) mutation in glp-1 /Notch produce half the normal number of adult germline progenitors, virtually all these single mutant animals are fertile. However, glp-1 (rf) rsks-1 (null) double mutant animals are all sterile, and in about half of their gonads, all GSCs differentiate, a distinctive phenotype associated with a significant reduction or loss of GLP-1 signaling. How rsks-1 /S6K promotes GSC fate is unknown. Here, we determine that rsks-1 /S6K acts germline-autonomously to maintain GSCs, and that it does not act through Cyclin-E or MAP kinase in this role. We found that interfering with translation also enhances glp-1 (rf), but that regulation through rsks-1 cannot fully account for this effect. In a genome-scale RNAi screen for genes that act similarly to rsks-1 /S6K, we identified 56 RNAi enhancers of glp-1 (rf) sterility, many of which were previously not known to interact functionally with Notch. Further investigation revealed at least six candidates that, by genetic criteria, act linearly with rsks-1 /S6K. These include genes encoding translation-related proteins, cacn-1 /Cactin, an RNA exosome component, and a Hedgehog-related ligand. We found that additional Hedgehog-related ligands may share functional relationships with glp-1 /Notch and rsks-1 /S6K in maintaining germline progenitors.